ENGLISH SPYCRAFT PROFESSIONALISMS AS A LINGUISTIC PHENOMENON - Lahodynskyi, Oleksandr; Mamchur, Kostyantyn; Skab, Volodymyr (Advanced Education, 2018)
The article defines and classifies English Spycraft professionalisms (ESP) as lexical units denoting main espionage concepts. It establishes that, because of inconsistency with the ‘terminology’ requirements (basically, lack of exact definitions, abundance of synonyms, and connotation colourings), these lexical units can be placed only under ‘professionalisms’ category. They include vocabulary with various degrees of formality: from official to very colloquial. The article also provides detailed ESP morphological and semantic analyses. Morphology demonstrates the three basic groups of ESP building means: compounding (formation of ESP complex phrases with several words of different parts of speech), affixation (using prefixes and suffixes), and abbreviation (shortening of Spycraft words and phrases of different kinds). Semantics finds out metaphor and metonymy as conversion means of ESP formation. The most frequently occurring metaphors across ESP are those of personification, process, container, time, animation and orientation. Metonymy is used among the ESP to figuratively name facts from espionage activity. All the ESP linguistic peculiarities are clearly illustrated by a large number of up-to-date examples derived from various English language open access resources. These examples were carefully singled out and collected as a research vocabulary corpus to be entered into the dictionary being prepared for the publication in the nearest future.